Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. Role of School Administration Towards Caring Gifted Students in Model Secondary Schools in Aden Governorate from the Teachers’ Point of ViewCo-Prof. Fahad Ali Abdullah , Dr. Dhahiba Saeed Saleh2. The role of the national case management system in achieving protection for vulnerable children  in the Republic of Yemen 2024 AD-1446AHMr. Abdulghani Abdulaziz Abdu Naji Al-Humaidi3. Analysis of the Educational Policy Document in the Kingdom of Saudi Arabia  in Light of Global Future Trends in EducationMs. Wardah Ali Al-Rzouq, Ms. Hamida Ahmed Al-Zakari, Prof. Fatima Abdullah Al-Bishr4. The impact of using generative artificial intelligence applications on developing digital educational content creation skills and the attitudes of female trainers and trainees  at the Girls' Technical College towards themMs. Imtinan Mohammed Alzughaibi, Co-Prof. Leena Ahmed Alfarani5. Educational signification extracted from the verses of mother in the holy Quran and their applications in the familyMs. Nourah Dakhel Al-Nefaie6. The Relationship between Intelligence Quotient with Variables among Kindergarten Children  in Khartoum StateDr. Nada Izzeldeen Jafar7. Suicide ideation among Sudanese adults cross in Khartoum state SudanDr. Radwa Mohamad Ibrahim, Dr. Fath-Alrhman Omer Alsharif, Dr. Nadir Elzain Omara
Keywords: Journal of Educational and Psychological Sciences